Preservation of keratinized gingiva around dental implants using a diode laser when uncovering implants for second stage surgery - Ra'ed Mohammed Ayoub Al-delayme (Istanbul University, 2019)
Purpose: The aim of the present study was to assess if a 940-nm diode laser or a traditional scalpel approach is more effective in minimizing patient comfort and postoperative sequelae, preserving peri-implant keratinized mucosa, and in enhancing impression quality after uncovering dental implants. Materials and methods: We designed a prospective, split mouth, single blinded, randomi¬zed controlled trial with patients who needed uncovering of dental implants. Our analysis included 388 implants in 73 patients. Split mouth technique was used to compare two approaches for uncovering implants: laser study group vs. scalpel control group. Patients were evaluated for intra- and post-operative pain and bleeding. At 1, 2, and 3 weeks post procedure patients in both groups were rechecked for postoperative sequelae, keratinized mucosal thickness quality and quantity, and accuracy of the implant emergence profile. Results: The laser study group showed that there was a reduction in postoperative pain and bleeding that was statistically significant in comparison to the control group. There were also statistically significant differences in gingival color and presence or absence of soft tissue edema and in the gingival was emergency profile between the laser and scalpel sides at 1, 2, and 3 weeks' post-procedure. Statistically significant differences (p< 0.001) were observed between the two groups in the criteria of ideal or satisfactory soft tissue projection in the gingival emergency profile, which indicates that impressions can be taken immediately or within 1 week after laser surgery. Conclusion: Uncovering dental implants using a diode laser operating at the wavelength of 940 ±10 nm, and a power output of 0.4-10 W is recommended for preparing an accurate implant emergence profile. Laser treatment can also effectively preserve keratinized mucosa around implants in comparison to the conventional scalpel technique.